Frontispiece: Palladium Catalysis for Aerobic Oxidation Systems Using Robust Metal–Organic Framework. Issue 48 (18th November 2019) - Li, Jiawei; Liao, Jianhua; Ren, Yanwei; Liu, Chi; Yue, Chenglong; Lu, Jiaming; Jiang, Huanfeng
Abstract : Heterogeneous Catalysis In their Communication on page 17148 ff., Y. Ren, H. Jiang et al. immobilize Pd II and Cu II species in a robust metal–organic framework to facilitate Pd catalysis for a desulfitative oxidative coupling reaction with high efficiency, low catalyst loading, and reusability.